Comparing Feed-In-Tariffs and Renewable Obligation Certificates - a Real Option Approach - Tim Mennel; Sara Scatasta (Verein für Socialpolitik, 2010)
The increase of the share of renewable energy in total energy production is a stated goal of environmental and industrial policy in many developed countries. Governments adopt regulation to support the investment into renewable energy infrastructure, in particular in power generation. Two main policy instruments emerge: renewable quotas and feedin-tariffs. Quota systems, such as the British ROCs, oblige an electricity producer to certify that a fixed share of his electricity is 'green', i.e. generated from renewable sources. Feed-in-tariffs, such as the German EEG tariffs, guarantee a certain, fixed price for 'green' electricity, depending on the technology. The decisive difference between the instruments is the allocation of price risk. The paper presents a real option framework to study the effect the instruments on investment and innovation of renewable energy plants. The modelled is calibrated on data for German Wind power plants. We find that the propensity to invest is higher under a quota system. So the presence of price risk spurs technological innovation.
Keywords: Q28; R48; H23; 330; Renewable Energy; Investment support policy; Real Options